A Snap Shot of Commercial Dairy Farmers in Jaffna District - Umashankar, K.; Barthipan, G. (Faculty of Agriculture University of Jaffna, Sri Lanka, 2010)
Protein plays a vital role in the formation of human diets. Protein deficiency has long been recognized for more than a century around the world. Dairy milk has been playing an important role in fulfilling the protein requirements of the people in Sri Lanka. But the Sri Lankan national dairy milk production is found to be far below the national requirement. Hence this research has taken attempt to identify the socio-economic determinants of the commercial dairy milk producers and quantify the current technical efficiency status of the commercial dairy industry of Valikamam area located in the Jaffna district, Sri Lanka. The purposive random sampling consisted around 18% of the population. The primary data were collected by a structured questionnaire. The data were analyzed within the framework of Cobb-Douglas production function and stochastic frontier production function by using the STATA 10 and FRONTIER 4.1. The capital investment, cost of concentrate feeds, cost of energy and the availability of pasture are found to be significant and increase the milk production by 0.091, 0.163, 0.132 and 0.198 percents respectively. The hours of labors, herd size and health care cost manifested a significant negative impact and decrease the milk production by 0.139, 0.204 and 0.08 percents respectively. The mean technical efficiency of Valikamam dairy farmers was estimated to be 66% and this manifested that the Valikamam farmers still have room for improvements
Keywords: Technical efficiency; Stochastic frontier production approach; Jaffna